1997
DOI: 10.3109/10623329709053394
|View full text |Cite
|
Sign up to set email alerts
|

Expression of a Chemotactic Cytokine (MCP-1) in Cerebral Capillary Endothelial Cells in Vitro

Abstract: A full-length cDNA encoding the porcine monocyte chemoattractant protein-1 (pMCPC-1) was isolated from growth-stimulated porcine cerebral capillary endothelial cells (cEC); the pMCP-1 cDNA showed 89% identity to human MCP-1 and was isolated by use of subtractive hybridization and differential screening of two phenotypically different sub-populations of cloned cEC. pMCP-1 was abundantly expressed in cEC grown in the presence of FCS, ECGF and heparin whereas lower expression was observed in cEC kept in FCS-suppl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Constitutive expression of CCL2 mRNA has been previously reported in porcine brain EC with upregulation upon stimulation with TNF-α [41]. In vitro studies using rat brain and retinal EC lines showed constitutive expression of CCL2 and increased release into the media following activation with TNF-α, IL-1β and IFN-γ [42].…”
Section: Discussionmentioning
confidence: 92%
“…Constitutive expression of CCL2 mRNA has been previously reported in porcine brain EC with upregulation upon stimulation with TNF-α [41]. In vitro studies using rat brain and retinal EC lines showed constitutive expression of CCL2 and increased release into the media following activation with TNF-α, IL-1β and IFN-γ [42].…”
Section: Discussionmentioning
confidence: 92%
“…Nitric Oxide Janigro et al, 1994Shukla et al, 1996Bolanos and Almeida, 1999Fischer et al, 1999Fukumura et al, 2001Thiel and Audus, 2001 Proinflammatory Cytokines Clark et al, 1995de Vries et al, 1996 del Zoppo, 1997Zach et al, 1997Gong et al, 1998Weiss et al, 1998Yang et al, 1999Prat et al, 2001del Zoppo and Mabuchi, 2003Kato et al, 2003Harhaj and Antonetti, 2004Lu et al, 2006Huang et al, 2006Yenari et al, 2006Calcium Shasby and Shasby, 1986Stuart et al, 1994Abbruscato and Davis, 1999aPark et al, 1999Brown and Davies, 2002Brown et al, 2004 BBB leakage is known to trigger the activation of astrocytes (Dietrich et al, 1994;Hirano et al, 1994). Glial fibrillary acidic protein (GFAP) is a specific marker of astrocytes and its upregulation is a hallmark of reactive astrocytes.…”
Section: Table 2 Mediators Of Bbb Disruption In Hypoxic-ischemic Conmentioning
confidence: 97%
“…Microglial cells and astrocytes are activated in response to hypoxia-ischemia (Kato et al, 2003;Lu et al, 2006;Yenari et al, 2006). Activated glia and endothelial cells produce chemokines and cytokines that enhance the lymphocyte migration across the BBB and also increase the permeability of the blood vessels (Zach et al, 1997;Gong et al, 1998;Weiss et al, 1998;Prat et al, 2001). In vitro studies have also shown that cytokines like tumour necrosis factor (TNF-), interferon (IFN-), interleukin-1 (IL-1 ), and IL-6 produced by perivascular microglia and astrocytes after injury or inflammation interrupts the BBB by disrupting the endothelial TJ (de Vries et al, 1996).…”
Section: Hypoxia-ischemia and Inflammationmentioning
confidence: 99%
“…Cultured brain endothelial cells were shown to express mRNA for MCP-1. Treatment with TNFa increased MCP-1 expression in a dose-dependent manner (Zach et al, 1997). Bovine brain microvessel endothelial cells showed increased expression of IL-8 after infection with bacterial parasite C. ruminantium (Bourdoulous et al, 1995).…”
Section: Chemokine Expression By Cns Cells In Vitromentioning
confidence: 99%